Fluorimetric Immunoassay for Multianalysis of Aflatoxins - Lizy Kanungo; Sunil Bhand (Journal of Analytical Methods in Chemistry)
A sensitive fluorimetric ELISA was developed for the analysis of aflatoxins. The assay was performed in a 384 microwell plate, wherein high specificity monoclonal antibody against AFM1 (mAb-AFM1) was used as capture antibody and FITC conjugated secondary antibody was used for detection and quantification of the analyte. The linear range of the immunoassay was found to be 6.25–50 pg/mL. AFM1 as low as 1 pg/mL was detected by this method with assay volume 40 μL. The multi-analysis of different aflatoxins was also investigated in the microwell plate, based on the cross-reactivity (CR) approach. Real milk samples were tested along with certified reference material by standard addition method and recovery analysis was done. The mAb-AFM1 showed 23.2% CR with AFB1, 50% CR with respect to AFM2, and least CR towards AFG1 (<1%). Furthermore, mixture analysis of AFM2 and AFB1 was carried out at specific concentrations of AFM1. The advantages of this developed immunoassay are high sensitivity, high throughput, multianalyte detection, versatility, and ease of handling.